Éléments pour une biocritique - Gisèle Séginger (Flaubert: Revue Critique et Génétique)
Flaubert’s letters in the 1850s defend the idea of a Science of Man inspired by the natural sciences and an expository Literature that would practice scientific criticism. The logic of the organic living world is what inspires him with these reflections. Flaubert’s formulation reveals a manipulation of knowledge and of epistemological transgressions when the texts condense ideas borrowed from different sciences. Biocriticism can designate first of all the criticism defended by Flaubert by legitimizing it with a conception of historicity of the living. Then on the level of our own analysis, a dynamic approach to the literary treatment of the knowledge of living matter: at the center of the attention the focus would not be on the enunciation, the content of speeches in themselves, but rather, on the logic and dynamics generated by their use in the texts, the tensions, diversions, reversions and what is thought or rethought.